The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1111/j.1476-5381.1984.tb16539.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic inhibitory receptors in pulmonary parasympathetic nerves in the guinea‐pig

Abstract: 1 In anaesthetized guinea-pigs, gallamine produced a dose-related potentiation of the bronchoconstriction induced by electrical stimulation of the cervical vagus nerves; (+)-tubocurarine and suxamethonium lacked this effect. 2 The bronchoconstriction produced by intravenous injection of acetylcholine or histamine, however, was not potentiated by gallamine. 3 Vagally-induced bradycardia was abolished by gallamine, confirming antagonism of the effect of acetylcholine on muscarinic receptors in the heart. 4 The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
207
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(221 citation statements)
references
References 10 publications
10
207
4
Order By: Relevance
“…One reason for the abnormality of the neural control of the airway smooth muscle is the loss of M2 receptor function (M2R). The M2Rs act by limiting the release of acetylcholine (Ach) onto the smooth muscle M3R (39). Thus, loss of M2R leads to uncontrolled smooth muscle contraction and subsequent bronchoconstriction as seen in asthma (40).…”
Section: Tissue Localization and Activation Status Of The Eosinophil mentioning
confidence: 99%
“…One reason for the abnormality of the neural control of the airway smooth muscle is the loss of M2 receptor function (M2R). The M2Rs act by limiting the release of acetylcholine (Ach) onto the smooth muscle M3R (39). Thus, loss of M2R leads to uncontrolled smooth muscle contraction and subsequent bronchoconstriction as seen in asthma (40).…”
Section: Tissue Localization and Activation Status Of The Eosinophil mentioning
confidence: 99%
“…Contractions were induced by electrical field stimulation (EFS) or by increasing concentrations of methacholine (MCh) as previously described (30). Neuronal M 2 muscarinic receptor function was tested in human tracheal smooth muscle by measuring the ability of gallamine, a selective antagonist, to potentiate EFSinduced contractions (19). Additional details are provided in the online supplement.…”
Section: Bronchoalveolar Lavage and Morphologic Study Of Lungmentioning
confidence: 99%
“…In the lungs, M 2 muscarinic receptors limit acetylcholine (ACh) release from parasympathetic nerves (16)(17)(18), thereby limiting vagally induced bronchoconstriction (19,20). Dysfunctional M 2 muscarinic receptors on airway parasympathetic nerves result in airway hyperresponsiveness in humans with asthma (21)(22)(23) and in animal models of asthma (24)(25)(26).…”
mentioning
confidence: 99%
“…Loss of function of inhibitory muscarinic autoreceptors is characterized by airway hyperresponsiveness to electrical stimulation of the vagus nerve. Furthermore, airway hyperresponsiveness to histamine in antigen challenged guinea pigs is due to increased vagally mediated reflex bronchoconstriction as a result of M2 receptor dysfunction (1)(2)(3)(4). It has been demonstrated that both in humans and in experimental animals the airway hyperresponsiveness, observed during viral infections, is the result of increased reflex bronchoconstriction due to inhibition of M2 muscarinic receptors.…”
Section: Introductionmentioning
confidence: 99%